2018
DOI: 10.1016/j.adolescence.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sleep insufficiency one year after high school

Abstract: This study captures sleep habits of adolescents one year after high school regardless of school and/or working status. Implications and future directions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Interestingly, parental education level was associated with shorter sleep duration [51]. This may be due to Korean parents' extraordinary interest in their children's academic achievement and parental involvement including private tutoring time, which may be related to sleep alterations in adolescent students [42,43,52].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, parental education level was associated with shorter sleep duration [51]. This may be due to Korean parents' extraordinary interest in their children's academic achievement and parental involvement including private tutoring time, which may be related to sleep alterations in adolescent students [42,43,52].…”
Section: Discussionmentioning
confidence: 96%
“…The numerous health and academic-related consequences of sleep problems make sleep, particularly during emerging adulthood, a public health concern. 14 College students experience unique challenges at the beginning of campus life (eg experiencing an unfamiliar environment, being responsible for oneself for the first time, academic stress, and living in a dormitory with students from different regions and cultures), all of which influence, or even heavily change, their sleep styles and sleep quality. The prevalence of poor sleep quality and the average PSQI score in our study were similar to those reported in previous studies of Chinese college students.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Adolescent behavioral habits, including sleep, tend to persist into adulthood. 14 However, high school students in China are among the most sleep-restricted population. Despite the increasing evidence of the detrimental effects of sleep loss in students, little has considered their exact school stages as modifiers of sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate potential determinants of physical fitness performance (main outcome), we fitted a series of simple (i.e., one independent variable at a time) and multiple (i.e., two or more independent variables simultaneously included in the same model) regression models. In detail, the fitted ordinary least squares regression models included the physical fitness performance score (continuous) as the dependent variable and the following independent variables: body fat percentage, mid-upper arm circumference, astronomical season, site and level of recreational physical activity, frequency of alcohol consumption, frequency of soda consumption, frequency of snack consumption, frequency of fruit consumption, smoking, adequacy of sleeping hours (sufficient ≥ 7 or insufficient < 7 h) 50 , frequency and hours spent per session of gaming/TV-watching, hemoglobin, creatinine and total 25-OH-vitamin D. The best multiple (main-effects) model was selected using the Akaike Information Criterion (AIC) combined with clinical plausibility. Given that our main focus was on vitamin D, we also examined all the regression models presenting pairwise interaction terms, including total 25-OH-vitamin D, as one of the two variables.…”
Section: Methodsmentioning
confidence: 99%